Study of the influence of the aluminum source (acetate or sulfate) on the synthesis of the ceramic membrane and applications of emulsion oil water: use and reuse (Research, Society and Development, 2021)
The objective of this work was to prepare ceramic membranes and to evaluate the effect of the raw material on the ceramic membrane and on the efficiency of the emulsion separation oil/water. The ceramic membranes were manufactured using the uniaxial dry compaction method, from the thermal decomposition of aluminum sulfate or aluminum acetate, to evaluate the effect of the raw material (aluminum acetate or aluminum sulfate) on the efficiency in the emulsion oil/water separation. Ceramic membranes were characterized by measurements of X-ray diffraction patterns, scanning electron microscopy, mechanical strength, bubble point and water flow. In this study, membranes were produced with different characteristics. The values found for the permeate for the A1 membrane were 9.20 mg / L due to characteristics such as porosity and mechanical strength (44.63 % and 1.3 MPa), while the values A2 membrane was 6.52 mg / L, 18.86 % and 6.7 MPa. In conclusion, the membranes prepared are effective in removing the oil from the oily waste water. According to the results, the treatment of oil-water emulsions by microfiltration facilitates a significant reduction in the concentration of permeate oil.